Applying the behavioural change wheel to guide the implementation of a biopsychosocial approach to musculoskeletal pain care - Ng, Wendy; Beales, Darren; Gucciardi, Daniel F.; Slater, Helen (Frontiers in Pain Research, 2023)
Achieving high value, biopsychosocial pain care can be complex, involving multiple stakeholders working synergistically to support the implementation of quality care. In order to empower healthcare professionals to assess, identify and analyse biopsychosocial factors contributing to musculoskeletal pain, and describe what changes are needed in the whole-of-system to navigate this complexity, we aimed to: (1) map established barriers and enablers influencing healthcare professionals' adoption of a biopsychosocial approach to musculoskeletal pain against behaviour change frameworks; and (2) identify behaviour change techniques to facilitate and support the adoption and improve pain education. A five-step process informed by the Behaviour Change Wheel (BCW) was undertaken: (i) from a recently published qualitative evidence synthesis, barriers and enablers were mapped onto the Capability Opportunity Motivation-Behaviour (COM-B) model and Theoretical Domains Framework (TDF) using “best fit” framework synthesis; (ii) relevant stakeholder groups involved in the whole-of-health were identified as audiences for potential interventions; (iii) possible intervention functions were considered based on the Affordability, Practicability, Effectiveness and Cost-effectiveness, Acceptability, Side-effects/safety, Equity criteria; (iv) a conceptual model was synthesised to understand the behavioural determinants underpinning biopsychosocial pain care; (v) behaviour change techniques (BCTs) to improve adoption were identified. Barriers and enablers mapped onto 5/6 components of the COM-B model and 12/15 domains on the TDF. Multi-stakeholder groups including healthcare professionals, educators, workplace managers, guideline developers and policymakers were identified as target audiences for behavioural interventions, specifically education, training, environmental restructuring, modelling and enablement. A framework was derived with six BCTs identified from the Behaviour Change Technique Taxonomy (version 1). Adoption of a biopsychosocial approach to musculoskeletal pain involves a complex set of behavioural determinants, relevant across multiple audiences, reflecting the importance of a whole-of-system approach to musculoskeletal health. We proposed a worked example on how to operationalise the framework and apply the BCTs. Evidence-informed strategies are recommended to empower healthcare professionals to assess, identify and analyse biopsychosocial factors, as well as targeted interventions relevant to various stakeholders. These strategies can help to strengthen a whole-of-system adoption of a biopsychosocial approach to pain care.